Benefits and limitations of block periodized training approaches to athletes' preparation: A Review - Issurin, V. B. (Sports Medicine, 2016)
The present review introduces innovative concepts of training periodization and summarizes a large body of findings characterizing their potential benefits and possible limitations. Evidence-based analysis of the traditional periodization model led to elaboration of alternative versions of athletic preparation. These alternative versions postulated the superiority of training programs with a high concentration of selected workloads compared with traditionally designed plans directed at the concurrent development of many athletic abilities at low/medium workload concentration. The training cycles of highly concentrated specialized workloads were coined "training blocks" by experts and practitioners; correspondingly, the alternative versions were termed "block periodized (BP) preparation systems" by their presenters. Ultimately, two BP training models were proposed: a concentrated unidirectional training model (CU) and a multi-targeted BP approach to athletes` preparation. The first innovative version postulated administration of highly concentrated training means for enhancement of one leading fitness component, whereas the second version proposed the development of many targeted abilities within sequenced block mesocycles containing a minimal number of compatible training modalities. Both versions differ in their methodological background, duration and content of training blocks, possibilities of providing multi-peak performances, and applicability to various sports. In recent decades, many studies have evaluated the effects of both BP training versions in different sports. Examination of the training effects producing by the CU model in combat and team sports has found significant gains in various fitness estimates but not in sport-specific performances. Similarly, utilization of a CU program by elite swimmers did not lead to substantial enhancement of their peak performances. In contrast, studies of multi-targeted BP training programs have revealed their distinct superiority compared with traditional preparation in endurance, team, and dual sports, and strength/power training and recreational athletes (28 studies). It is suggested that the CU training strategy suits athletic disciplines demanding one fitness component like explosive strength in jumping performances. Unlike this limitation, the multi-targeted BP system prompted a beneficial increase of specific preparedness in sports and disciplines in which peak performances require the application of many targeted athletic abilities.